Pengaruh Struktur Modal, Peluang Pertumbuhan, dan Produk Domestik Bruto terhadap Profitabilitas pada Perusahaan Pembiayaan yang Terdaftar di BEI Periode 2020-2022 - Sativani, Agri; Luh Gede Kusuma Dewi (Universitas Pendidikan Ganesha, 2024)
This research aims to analyze the effect of capital structure, growth opportunity, and Gross Domestic Product on profitability. The research type is associative quantitative research. The data used is secondary data from the company’s annual report that can be accessed through the official website of Indonesia Stock Exchange, namely www.idx.co.id and the official website of Central Bureau of Statistics (Indonesia), namely www.bps.go.id. The research population is all multifinance companies listed in Indonesia Stock Exchange for 2020-2022 period, as many as 25 companies. Based on the purposive sampling method, there are 12 multifinance companies as a research sample. The data obtained were then tested and analyzed by descriptive statistical analysis, classical assumption testing, as well as hypothesis testing by software of SPSS 26 version. The results of this research can be showed that: (1) capital structure does not affect profitability; (2) growth opportunity has a negative and significant effect on profitability; (3) Gross Domestic Product has a positive and significant effect on profitability; and then (4) capital structure, growth opportunity, and Gross Domestic Product simultaneously affect profitability.